GP129 The caries experience of children attending the national paediatric craniofacial centre (npcc), dublin, ireland. (June 2019) - Kelly, Mairéad; McGovern, Eleanor; Murray, Dylan
Abstract : Introduction: Children with craniofacial conditions would be considered to be at a higher risk of and from dental caries. Despite this high risk, there is limited data in the literature reporting on the dental caries experience of these children. For the last number of years children attending the National Paediatric Craniofacial Centre (NPCC) have been enrolled in the tertiary paediatric dental services by their first birthday. They are also referred to primary services for ongoing prevention of dental disease. The objective of this review was to determine the caries experience of a cohort of children attending the NPCC over an 18-month timeframe. Methods: The World Health Organisation examination criteria were used with the inclusion of visual caries. Dental caries was recorded using the dmft (decayed, missing and filled primary teeth) index (WHO, 1987). For the purposes of our study, a single, calibrated examiner (EMcG) carried out clinical examination and recorded the dmft score in the dental record of each child. Results: The dmft of the 33 children aged between 13 months and 8 years of age attending the NPCC was obtained, compiled in a dataset, and analysed. For all children in the cohort (n = 33), the average dmft was 1.2. Of the 33 children evaluated, 75.8% were caries free (dmft = 0) and 97% were dentally fit (dt = 0). The overall treatment index for this cohort was 94.7%. To compare to national values, the same parameters for 5-year olds were evaluated (n = 12). The mean dmft for this group was 1.3. Of this group, 66.67% were caries free, 91.67% were dentally fit and the overall treatment index was 87.5%. According to the National Survey, the dmft of 5-year-olds in the general population was 1.3. Conclusion: Children with craniofacial conditions may be at higher risk of dental caries than the general child population for a variety of reasons. The present study details the caries experience of children attending a single centre, the NPCC, across a broad age range. Our findings suggest that although the overall dmft of 5-year-old children in the study was equivalent to children of the same age in the National Survey, the treatment index of the children attending the NPCC far exceeds that of the general population (Whelton et al., 2002). It is reassuring to observe that across all age groups studied, a high proportion of the children in our cohort were dentally fit.